Systematic Review: Pengaruh Gaya Kepemimpinan Transformasional terhadap Kinerja Karyawan dalam Organisasi Kesehatan - Rahmadani, Arini Dwi; Nasution, Azra Muzaiyana; Sari, Dinda Purnama; Rambe, Raudhiyah Hasanah; Silaban, Sry Wulan; Wasiyem Wasiyem (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2026)
Employee performance plays a strategic role in determining service quality in healthcare organizations, thus requiring an effective leadership model to encourage increased motivation and work productivity. This study aims to examine the influence of transformational leadership on employee performance in the healthcare sector. The method used is a literature review with a qualitative descriptive approach through the analysis of ten scientific articles from 2020–2025 selected based on topic suitability, publication feasibility, and relevance to the healthcare context in Indonesia. The results of the study show that transformational leadership consistently has a positive impact on employee performance in all categories of health professions, both clinical and administrative staff, with increased work enthusiasm, job satisfaction, and work effectiveness as the main driving factors. Leaders who are able to inspire, establish effective communication, and pay attention to the conditions of each individual have proven to be able to create a work atmosphere that supports performance improvement. These findings emphasize the importance of healthcare organizations strengthening the implementation of transformational leadership through training, leadership competency improvement, and strengthening a conducive work culture in order to maximize employee performance.